Factors influencing enrollment intention in private schools - Ping, Lim Lee; Hee, Ong Choon; Kowang, Tan Owee; Yew, Lim Kim (International Journal of Evaluation and Research in Education (IJERE), 2025)
The growth in private school student enrollment in Malaysia has prompted institutions to upgrade to stay competitive in the market. However, despite the increasing number of private schools, regrettably, only a few studies have focused on the factors that influence private school enrollment. This study examines the relationship between social influences (SI), school environment (SE), characteristics, parent-administration-teacher relationship (PAT), and private school enrolment intention in Malaysia. It uses a quantitative method and G*Power to determine the minimum sample size. Data was gathered from 135 respondents who have enrolled at least one child in private schools using questionnaire surveys. The statistical package for social science (SPSS) was used to analyze the data. The results showed that SI and school characteristics (SC) significantly and positively correlated with enrolment intention. The PAT was not significantly associated with enrolment intention. This study clearly shows that SI factors and SCs are crucial for enrolment intention in private schools. The management should develop and implement marketing strategies that effectively tackle current market challenges by focusing on SI and improving the SC. They can tailor the marketing strategy with electronic word-of-mouth (e-WOM) for SI and apply learning analytics for SC.